2023
DOI: 10.3389/fimmu.2023.1049536
|View full text |Cite
|
Sign up to set email alerts
|

AFM negatively regulates the infiltration of monocytes to mediate sepsis-associated acute kidney injury

Abstract: BackgroundSepsis is organ dysfunction due to the host’s deleterious response to infection, and the kidneys are one of the organs damaged in common sepsis. Sepsis-associated acute kidney injury (SA-AKI) increases the mortality in patients with sepsis. Although a substantial volume of research has improved the prevention and treatment of the disease, SA-SKI is still a significant clinical concern.PurposeAimed to use weighted gene co-expression network analysis (WGCNA) and immunoinfiltration analysis to study SA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…It includes 39 AKI and 9 normal control samples, we found 956 DEGs (including 478 up regulated genes and 478 down regulated genes). Studies suggested that PLG (plasminogen) [53], AFM (afamin) [54] and UMOD (uromodulin) [55] are involved in advancement of AKI. PLG (plasminogen) [56], GSTA1 [57], AGTR1 [58], CYP4A11 [59], UMOD (uromodulin) [60] and IL1RL1 [61] might be a potential prognostic markers or therapeutic targets against the cardiovascular disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It includes 39 AKI and 9 normal control samples, we found 956 DEGs (including 478 up regulated genes and 478 down regulated genes). Studies suggested that PLG (plasminogen) [53], AFM (afamin) [54] and UMOD (uromodulin) [55] are involved in advancement of AKI. PLG (plasminogen) [56], GSTA1 [57], AGTR1 [58], CYP4A11 [59], UMOD (uromodulin) [60] and IL1RL1 [61] might be a potential prognostic markers or therapeutic targets against the cardiovascular disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Studies had shown that PLG (plasminogen) [69], GSTA1 [70], AGTR1 [71] and CYP4A11 [72] were associated with liver disease. PLG (plasminogen) [73], AFM (afamin) [54], AGTR1 [74] and UMOD (uromodulin) [75] might be a potential therapeutic target for sepsis. Abnormal regulation of PLG (plasminogen) [76], AFM (afamin) [77], GSTA1 [78], AGTR1 [79] and UMOD (uromodulin) [80] are associated with diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes migrate into the injured kidney and differentiate into macrophages, further infiltrating tissue and aggravating ischemic murine ischemic renal injury by secreting pro-inflammatory cytokines interleukin (IL)-6, tumor necrosis factor-α, and IL-1β [28][29][30]. Another experimental study by Guo et al found that decreased expression of the gene AFM could lead to increased monocyte infiltration, thereby promoting renal inflammation and injury in murine models of sepsis-associated AKI [31]. Furthermore, it has been demonstrated that regulatory T lymphocytes (Treg) could exert protective effects in AKI, reducing inflammation and promoting tissue repair through the anti-inflammatory cytokine IL-10-mediated suppression of the innate system [32].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from serum and urinary biomarkers, there is ongoing research regarding molecular biomarkers of SA-AKI. In particular, gene expression profiles in SA-AKI together with biomarkers stemming from proteomics and metabolomics have revolutionized the field of SA-AKI in terms of diagnosis and prognosis [ 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Regarding gene expression profiles, Guo et al have very recently demonstrated that the AFM gene, also called “afamin”, which is a member of the albumin family of genes, may be a surrogate biomarker for SA-AKI.…”
Section: Biomarkers In Sa-akimentioning
confidence: 99%
“…Regarding gene expression profiles, Guo et al have very recently demonstrated that the AFM gene, also called “afamin”, which is a member of the albumin family of genes, may be a surrogate biomarker for SA-AKI. More specifically, using the Gene Expression Omnibus (GEO) Synthesis database and Weighted Gene Co-expression Network Analysis (WGCNA), they documented afamin as a biomarker of SA-AKI being inversely associated with the recruitment of monocytes and the levels of various inflammatory factors [ 57 ]. By using the GEO database as well, Liu et al found that 7 out of the 15 hub genes are involved in the enriched Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway.…”
Section: Biomarkers In Sa-akimentioning
confidence: 99%